Museums, intangible cultural heritage, and changing societies: The Ber gi dala exhibition and cultural heritage preservation at the Kisumu museum, Kenya - Luby, Edward M; Onjala, Isaya O.; Mitei, Daniel kibet arap (John Wiley & Sons, Inc, 2017)
The aim of this article is to give an account of the Ber gi dala exhibition at the Kisumu Museum, Kenya. It focuses on the customs, traditional buildings, and intangible cultural heritage of one of the major tribal groups in Kenya, the Luo. The development and use of this innovative exhibition, insofar as it recreates traditional Luo homesteads is first analysed. The exhibition's relevance in the framework for preserving and interpreting intangible cultural heritage is then discussed. Lastly, the exhibition's role as a model for presenting relevant museum‐based, community‐oriented heritage preservation initiatives in a place undergoing rapid change is highlighted in the final section.